The use of staff policy recommendations in central banks - Attila Csajbók (Magyar Nemzeti Bank, 2008)
The focus of this paper is on the use of staff policy recommendations in central banks. Based on the responses to a recent survey conducted by the Bank of International Settlements, the paper tries to answer two questions. (1) How (to what extent) do central bank decision-makers make use of staff views regarding the appropriate policy? (2) What institutional features determine the extent to which staff policy views are utilised by decision-makers? The 'weight' with which staff policy views are taken into account is proxied by how explicitly they are presented to the policy board. Based on the survey responses about how staff policy views are presented, a Staff Recommendation Explicitness Index (SREI) is constructed for each central bank surveyed. SREI is then regressed on a number of candidate explanatory variables. The results suggest that the use of staff policy views, proxied by SREI, is negatively related to the size of the policy committee. Furthermore, the use of staff policy views seems more pronounced if the committee is consensus-seeker and if the monetary regime is inflation targeting. Tentative explanations are offered for each of these findings.
Keywords: D71; E58; 330; monetary policy; central bank staff; committee; decision-making; Geldpolitik; Arbeitskräfte; Entscheidung